The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00412-008-0148-6
|View full text |Cite|
|
Sign up to set email alerts
|

Production of diploid and triploid offspring by inbreeding of the triploid planarian Dugesia ryukyuensis

Abstract: Triploidy has generally been considered to be an evolutionary dead end due to problems of chromosomal pairing and segregation during meiosis. Thus, the formation of tetraploids and diploids from triploid types is a rare phenomenon. In the present study, we demonstrated that inbreeding of the triploid planarian Dugesia ryukyuensis resulted in both diploid and triploid offspring in nature. In the triploids of D. ryukyuensis, chiasmata between homologous chromosomes were observed in both female and male germ line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Stocchino et al 2012). Sexualised specimens of D. ryukyuensis differ from our fertile ex-fissiparous lineages also in that offspring in populations of the former species consisted of both fissiparous and sexual individuals (Kobayashi et al 2009(Kobayashi et al , 2012. The coexistence of sexual and asexual individuals in mixed populations rules out the occurrence of alternating stages of sexual and fissiparous reproduction in the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…Stocchino et al 2012). Sexualised specimens of D. ryukyuensis differ from our fertile ex-fissiparous lineages also in that offspring in populations of the former species consisted of both fissiparous and sexual individuals (Kobayashi et al 2009(Kobayashi et al , 2012. The coexistence of sexual and asexual individuals in mixed populations rules out the occurrence of alternating stages of sexual and fissiparous reproduction in the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…AqS worms, which are transformed from asexual to sexual worms, produce offspring that reproduce either asexually or sexually. In addition, AqS worms can reproduce by genetic cross-mixing (Kobayashi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To prepare metaphase spreads of mitotic chromosomes for imaging, a previously published hybridization protocol was followed (Kobayashi et al, 2008). The preparations were dried overnight and stored at -80°C.…”
Section: Chromosome Preparation and Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…We have previously demonstrated that diploid and triploid offspring are produced in a ratio of 1:2 or 1:3 with a significance level of 5% (see table 1 in Kobayashi et al 2008). In the present study, to examine the relationship between polyploidy and the mode of reproduction in the offspring, karyological investigations were conducted on asexual and sexual offspring derived from the same cocoons (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have demonstrated that inbreeding of the acquired sexuals results in both diploid and triploid offspring. Recent studies have indicated that meiosis occurs in both female and male germ lines in acquired sexuals, which undergo sexual reproduction (Kobayashi et al 2008). The mechanisms that determine the reproductive mode in planarians are poorly understood (Grasso & Benazzi 1973;Benazzi 1974;Benazzi & Benazzi 1976;Baguñà et al 1999).…”
Section: Introductionmentioning
confidence: 99%